2009
DOI: 10.1136/emj.2008.064428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of acute coronary syndrome in patients with chest pain and a normal or non-diagnostic electrocardiogram

Abstract: Background: Clinical features may be used to determine which patients with suspected acute coronary syndrome (ACS), but a normal or non-diagnostic ECG, should be selected for further investigation or inpatient care. We aimed to measure the diagnostic value of clinical features for ACS. Methods: Standardised data relating to presenting characteristics, associated features and risk factors were collected at seven chest pain units established for the ESCAPE trial. All patients received troponin measurement at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Silent ECG and coronary occlusions involving the circumflex coronary artery, the distal LAD or minor branches such as diagonals or marginal branches have been described elsewhere 5 6. In our case though it was the proximal LAD that was occluded over the first 50 mm of its proximal portion on coronary angiography.…”
Section: Discussionmentioning
confidence: 46%
“…Silent ECG and coronary occlusions involving the circumflex coronary artery, the distal LAD or minor branches such as diagonals or marginal branches have been described elsewhere 5 6. In our case though it was the proximal LAD that was occluded over the first 50 mm of its proximal portion on coronary angiography.…”
Section: Discussionmentioning
confidence: 46%
“…As this was a planned substudy, no formal power calculation was undertaken, however previous observational studies reporting the diagnostic utility of chest pain characteristics have typically recruited upwards of 400 participants (13,14,(16)(17)(18)(19). Chi-squared analyses were used to generate 2 x 2 tables for the calculation of sensitivity, specificity, 95% confidence intervals are reported.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, evidence examining the value of typical symptoms in patients presenting with chest pain in the acute setting have demonstrated a poor correlation with the final diagnosis of acute coronary syndrome (3,(13)(14)(15)(16)(17)(18)(19). However, these studies have tended to either include patients with diagnostic ECG changes , focus on specific chest pain characteristics rather than overall typicality, or use M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 research nurses to extract this information.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified clinical features that predict the likelihood of acute coronary syndromes, such as chest pain being "indigestion-like" or "burning" in character; radiation to either arms, neck or shoulder; precipitation by exertion, presence of a third heart sound and hypotension, 9e11 but most of these studies involved patients with diagnostic ECGs or confirmed acute coronary syndromes where the diagnosis is clearer. In contrast, a recent study involving patients with normal or non-diagnostic ECGs reveal that isolated clinical features have very limited diagnostic value, 12 and measurement of troponin is therefore of paramount importance. Evidence is lacking as to which groups of clinical features predict patients with chest pain who are likely to have undetectable troponin concentrations in the context of a normal or nondiagnostic ECG, where the aetiology is in doubt.…”
Section: Introductionmentioning
confidence: 92%